Pengaruh Tegangan Pompa Bahan Bakar Terhadap Kandungan Emisi Gas Buang - Mufdi Ashadrul Aldi Pane; Wakhinuddin S -; Dwi Sudarno Putra; M Nasir - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2016)
Combustion emissions from millions of exhaust coming out every day would cause problems because the impact on the air quality and the problems of chronic diseases when inhaled by humans. This study wants to reveal the influence of variations in electric voltage to the fuel pump exhaust emissions. The study was conducted using an experimental method, using a form of Post-test Only Control Design. The object being tested is a Toyota Avanza 1.3 GM / T. The voltage should be 12 V, the research varying the voltage to the level of 11 V, 10 V and 9 V. The results obtained, when the voltage is 12 V the average emissions of CO and HC 95.5ppm 0.187%. At a voltage of 11 V emissions down to 0.125% CO and HC 62.5ppm. However, when the voltage is 10V and 9V increased emissions. At 10 V variation 0.245% CO and HC 110.8ppm. At 9 V variation 0.303% CO and HC 139.2ppm.